Does the Ultrasonic Cleaning Medium Affect the Adhesion of Resin Cement to Feldspathic Ceramic? - Marques Nogueira Martins, Maria Elizabeth; Pereira Leite, Fabiola Pessoa; Cavalcanti Queiroz, Jose Renato [UNESP]; Vanderlei, Aleska Dias [UNESP]; Jose Feres Reskalla, Helcio Nagib; Oezcan, Mutlu (Quintessence Publishing Co Inc, 2012)
Purpose: To evaluate the effect of different cleaning media on the adhesion of resin cement to feldspathic ceramic after etching.Materials and Methods: The cementation surfaces of ceramic blocks (N = 20, n = 5 per group) were etched with 10% hydrofluoric acid (HF) gel for 20 s and rinsed for 60 s. They were then randomly assigned to 4 groups: G1: air-water spray+drying (control); G2: ultrasonic cleaning in distilled water for 4 min+drying; G3: ultrasonic cleaning in 99.5% acetone for 4 min+drying; G4: ultrasonic cleaning in 70% alcohol for 4 min+drying. The ceramic blocks were silanized and cemented (RelyX ARC) to the composite blocks. Subsequently, the microtensile bond strength test (mu TBS) was performed. In addition, EDS analysis was made to assess the elemental composition of the conditioned and cleaned ceramic surfaces.Results: A significantly higher mean mu TBS was obtained when specimens had been ultrasonically cleaned in distilled water (G2: 18.8 +/- 0.4 MPa) (p < 0.05) compared to other groups (G1: 16.6 +/- 0.5; G3: 16.1 +/- 0.9; G4: 15.8 +/- 1.4) (one-way ANOVA). EDS analysis indicated the presence of F- only in G1. Dissolved precipitates after HF etching were removed by ultrasonic cleaning.Conclusion: Cleaning the HF-etched ceramic surface ultrasonically in distilled water is recommended, instead of rinsing it with air-water spray only.
Keywords: adhesion; cementation; dental materials; microtensile bond strength; ultrasonic cleaning